Teknik Pembibitan Kayu Putih (Melaluca Cajuputi) Secara Vegetatif di Persemaian Perusahaan Batubara PT Bukit Asam (Persero) Tbk - Irdika Mansur; Muhd Indarwan Kadarisman (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2019)
Melaleuca cajuputi has an ability to sprout easily, this is one of indicator for plants that potentially could be reproduced productively. PT Bukit Asam Ltd. has used Melaleuca cajuputi as the main of tree species for the reclamation of its post-mining land. The seedlings are produced generatively using seeds. The purpose of this research was to determine responses of IBA and Growth Media on the tip cutting of Melaleuca cajuputi The results showed that 88.9% of the cuttings, 61.2% of the rooted, and 80.9% of the shoots were viable. The used of IBA and a variety of growing media did not significantly affect to life percentage, rooted percentage, shoots percentage, fresh weight and dry weight of root, fresh weight and dry weight of shoots, numbers of primary and secondary roots, length of primary roots, and length of shoots. The result of this research can be adopted by PT Bukit Asam Ltd. to shorten production time of Melaleuca cajuputi seedlings in the future, where the availability of seeds is limited.Keywords: IBA, Melaleuca cajuputi, cutting, mining